Selective use of sorafenib in the treatment of thyroid cancer - Pitoia F; Jerkovich F (Dove Medical Press, 2016)
Fabián Pitoia, Fernando Jerkovich Division of Endocrinology, Hospital de Clinicas – University of Buenos Aires, Buenos Aires, Argentina Abstract: Sorafenib is a multiple kinase inhibitor (MKI) approved for the treatment of primary advanced renal cell carcinoma and advanced primary liver cancer. It was recently approved by several health agencies around the world as the first available MKI treatment for radioactive iodine-refractory advanced and progressive differentiated thyroid cancer. Sorafenib targets C-RAF, B-RAF, VEGF receptor-1, -2, -3, PDGF receptor-β, RET, c-kit, and Flt-3. As a multifunctional inhibitor, sorafenib has the potential of inhibiting tumor growth, progression, metastasis, and angiogenesis and downregulating mechanisms that protect tumors from apoptosis and has shown to increase the progression-free survival in several Phase II trials. This led to the Phase III trial (DECISION) which showed that there was an improvement in progression-free survival of 5 months for patients on sorafenib when compared to those on placebo. Adverse events with this drug are common but usually manageable. The development of resistance after 1 or 2 years is almost a rule in most patients who showed partial response or stabilization of the disease while on sorafenib, which makes it necessary to think of a plan for subsequent therapies. These may include the use of another MKI, such as lenvatinib, the second approved MKI for advanced differentiated thyroid cancer, or include patients in clinical trials or the off-label use of other MKIs. Given sorafenib’s earlier approval, most centers now have access to its prescription. The goal of this review was to improve the care of these patients by describing key aspects that all prescribers will need to master in order to optimize outcomes. Keywords: multiple kinase inhibitor, differentiated thyroid cancer, progression-free survival, radioiodine